Kinematics based physical modelling and experimental analysis of the shoulder joint complex - Almeida-Galárraga, Diego; Ros-Felip, Antonio; Álvarez-Sánchez, Virginia; Marco-Martinez, Fernando; Serrano-Mateo, Laura (Ingeniería e Investigación, 2017)
The purpose of this work is to develop an experimental physical model of the shoulder joint complex. The aim of this research is to validate the model built and identify the forces on specified positions of this joint. The shoulder musculoskeletal structures have been replicated to evaluate the forces to which muscle fibres are subjected in different equilibrium positions: 60º flexion, 60º abduction and 30º abduction and flexion. The physical model represents, quite accurately, the shoulder complex. It has 12 real degrees of freedom, which allows motions such as abduction, flexion, adduction and extension and to calculate the resultant forces of the represented muscles. The built physical model is versatile and easily manipulated and represents, above all, a model for teaching applications on anatomy and shoulder joint complex biomechanics. Moreover, it is a valid research tool on muscle actions related to abduction, adduction, flexion, extension, internal and external rotation motions or combination among them.